Study on the evolution laws of overlying strata stress and mining-induced fracture zones under coordinated extraction in multi-working face areas - Bai, Xinkuan; Yuan, Qiang; Jiang, Qian; Song, Jun; Chen, Zhu; Liu, Xiaoliang (Frontiers in Earth Science, 2026)
With the continuous increase in coal mining depth and intensity, the stress distribution in surrounding rock during multi-working face coordinated mining has become increasingly complex, significantly affecting the safe and efficient extraction of coal resources. This study takes the 22,214 and 22,215 working faces in Liuta Mine as the engineering background and employs FLAC3D numerical simulation to analyze the evolution of mining-induced stress and overburden fracture characteristics during coordinated mining of two adjacent faces. By establishing the stress superposition intensity index Iσ and the plastic zone evolution index IP, the mechanisms of stress superposition and cumulative plastic damage in multi-working face mining were quantitatively revealed. Simulation results indicate that the stress and plastic zone in the first-mined face exhibit a symmetric distribution, with the peak abutment pressure increasing as the face advances, reaching a maximum stress concentration factor of 1.8. In contrast, the subsequent face, influenced by the adjacent goaf and the coal pillar and key stratum structure, shows significant asymmetry in both strike and dip stress distributions. The stress concentration factor on the coal pillar side reaches a maximum of 2.3, and the stress increment within 0–40 m ahead of the face is approximately 1.3–1.4 times that of the first-mined face. The multi-working face advance process demonstrates a three-stage evolution characterized by low superposition, medium superposition, and strong superposition. At an advance distance of 2,400 m, corresponding to the transition of the main key stratum from a suspended state to a fractured voussoir beam structure, the stage represents a strong superposition zone of stress and plastic deformation. In this zone, the plastic area on the coal pillar side connects with the goaf of the first-mined face, leading to a significant increase in the risk of surrounding rock instability. The study elucidates the mechanisms of stress transfer and plastic zone interconnection during coordinated multi-working face mining and identifies the strong superposition stage as a critical period for rockburst prevention and control. Accordingly, a combined strategy of differentiated support and directional pressure relief is proposed to maintain surrounding rock stability, with emphasis on monitoring the strong plastic deformation superposition zone. The findings provide a theoretical reference for mining-induced stress analysis, stability control of surrounding rock, and rockburst prevention under similar geological and mining conditions.